Engineering nanoparticle strategies for effective cancer immunotherapy - Yoon, Hong Yeol; SeIvan, Subramanian Tamil; Yang, Yoosoo; Kim, Min Ju; Yi, Dong Kee; Kwon, Ick Chan; Kim, Kwangmeyung (ELSEVIER SCI LTD, 2018)
Cancer immunotherapy has been emerging in recent years, due to the inherent nature of the immune system. Although recent successes of immunotherapeutics in clinical application have attracted development of a novel immunotherapeutics, the off-target side effect and low immunogenicity of them remain challenges for the effective cancer immunotherapy. Theranostic nanoparticle system may one of key technology to address these issues by offering targeted delivery of various types of immunotherapeutics, resulting in significant improvements in the tumor immunotherapy. However, appropriate design or engineering of nanoparticles will be needed to improve delivery efficiency of antigen, adjuvant and therapeutics, resulting in eliciting antitumor immunity. Here, we review the current state of the art of cancer immunotherapeutic strategies, mainly based on nanoparticles (NPs). This includes NP-based antigen/adjuvant delivery vehicles to draining lymph nodes, and tumor antigen-specific T-Iymphocytes for cancer immunotherapy. Several NP-based examples are shown for immune checkpoint modulation and immunogenic cell death. These overall studies demonstrate the great potential of NPs in cancer immunotherapy. Finally, engineering NP strategies will provide great opportunities to improve therapeutic effects as well as optimization of treatment processes, allowing to meet the individual needs in the cancer immunotherapy. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: IMMUNOGENIC CELL-DEATH; UP-CONVERSION NANOPARTICLES; ANTITUMOR IMMUNE-RESPONSES; LYMPH-NODE; CHECKPOINT BLOCKADE; PHOTODYNAMIC THERAPY; PHOTOTHERMAL THERAPY; ADJUVANT DELIVERY; CARBON NANOTUBES; PD-L1 EXPRESSION